Characterisation of the molecular mechanisms of multiple antibiotic tolerance in growth‐arrested Cronobacter sakazakii under ampicillin exposure. (31st March 2022) - Chen, Chuxin; Ao, Jialu; Wang, Li; Zhang, Jingfeng; Mo, Yunshao; Zhang, Yehui; Zhao, Lichao
Summary: Cronobacter sakazakii could enter a growth‐arrested state when exposed to ampicillin. Growth‐arrested bacteria can become more tolerant to a wide range of antibiotics, posing a serious threat to food safety and human health. The aim of this study was to investigate the tolerance of growth‐arrested C. sakazakii to a variety of antibiotics and to explore the underlying mechanisms responsible for the variations in antibiotic tolerance levels. The results of the study, as tested by flat colony counting method as well as PMAxx‐qPCR, showed that growth‐arrested C. sakazakii had higher tolerance to four different antibiotics. Results validated by RT‐qPCR indicated that almost all the changes in the expression of antibiotic resistance genes in growth‐arrested cells showed a tendency to promote antibiotic tolerance compared to culturable cells, with significant upregulation of expression of the multidrug efflux pump genes in particular. Furthermore, the up‐regulated gene expression of relA and rpoS and insignificant changes in gene expression of spoT suggested that the stringent response could positively regulate the multidrug efflux pumps of growth‐arrested cells. Growth‐arrested C. sakazakii pose a potential source of contamination and should be taken into account when monitoring of food safety. Abstract : Growth‐arrested Cronobacter sakazakii were more tolerant to multi‐antibiotics. Growth‐arrested cells mainly due to active efflux pumps against multi‐antibiotics. Stringent response might still positively regulate in growth‐arrested cells.